Molecular Characterization and Expression Profiling of Three Transformer-2 Splice Isoforms in the Redclaw Crayfish, Cherax quadricarinatus - Cai, Lina; Zheng, Jianbo; Jia, Yongyi; Gu, Zhimin; Liu, Shili; Chi, Meili; Cheng, Shun (Frontiers in Physiology, 2020)
Sex determination/sex differentiation is determined by genetics, environmental factors, or the interactions of both. The Transformer-2 (Tra-2) gene plays an important role in the sex determination cascade signal pathway in insects. In this study, the Tra-2 gene was isolated and characterized from the cDNA library of gonad tissues in the redclaw crayfish, Cherax quadricarinatus. Three splice variants were identified, designated as CqTra-2A, CqTra-2B and CqTra-2C, and sequence analysis showed that they had a highly conserved RRM domain. Phylogenetic analysis was performed by the NJ method and the results revealed that the Tra-2 protein of the redclaw crayfish was very close related to that of Macrobrachium rosenbergii, Fenneropenaeus chinensis and Macrobrachium nipponense. Real-time PCR analysis showed that the three isoforms were predominantly expressed in the ovary and gradually increased with embryonic development. Besides, the expression pattern of CqTra-2 at different developmental stages was analyzed by qPCR, and revealed that the phase of body length 3cm may be the key period for the sex differentiation of C. quadricarinatus. RNAi-targeting gene silencing further confirmed the function of CqTra-2 on sexual differentiation in redclaw crayfish. Our experimental data will contribute to understanding the mechanism of sex determination in crustaceans.